Peningkatan kesehatan ternak ruminansia kecil melalui pemberian antiparasit dan vitamin di Desa Petir, Kabupaten Bogor (Small ruminant health improvement by providing antiparasitic and vitamin in Petir Village, Bogor District) - Juara, Fanggy Malindo; Arif, Ridi; Mihardi, Arief Purwo (Universitas Syiah Kuala, 2023)
Goats and sheep are small ruminants that are widely used as livestock by the people of Indonesia. One of them is in Petir Village, Dramaga Sub-District, Bogor District. Increasing livestock productivity can be achieved by paying attention to aspects of livestock health. Ruminants often get infection by parasitic worms. Treatment of parasitic helminth infections can be carried out by the administration of anthelmintic and supportive treatment with vitamins administration. This activity aims to improve the health of small ruminants by administering anthelmintic to deworming and vitamins to support livestock productivity. This activity begins with the examination of fecal samples from livestock to diagnose parasitic helminth infections. The results of the examination are used as a basis for carrying out treatment in the form of administering deworming and vitamins. The results of the examination of fecal samples were obtained as many as 66.67% found of positive helminth infection and 46.67% positive of oocysts. Common clinical symptoms are found like have diarrhea and have thin bodies. Treatment has been carried in nine farms of sheep and goat in the village. This activity received support from residents, especially sheep and goat farmers. The anthelmintic and vitamin administration to small ruminants has been carried out well and is part of efforts to increase livestock productivity in Bogor District.